2022
DOI: 10.1186/s13059-022-02756-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into the evolutionary history and diversification of bulb traits in garlic

Abstract: Background Garlic is an entirely sterile crop with important value as a vegetable, condiment, and medicine. However, the evolutionary history of garlic remains largely unknown. Results Here we report a comprehensive map of garlic genomic variation, consisting of amazingly 129.4 million variations. Evolutionary analysis indicates that the garlic population diverged at least 100,000 years ago, and the two groups cultivated in China were domesticated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 56 publications
3
21
1
Order By: Relevance
“…The PBS method was proposed to detect a significant change in allele or haplotype frequency along the lineage of one population after it diverged from other populations. Many previous studies demonstrated its efficiency in detecting candidate selection signatures in a target population over short divergence times [ 47 49 ]. We finally identified 53,672 candidate selection windows specific to Beijing Black pig and discovered that DNAJC6 and RUFY4 are related to meat quality traits.…”
Section: Discussionmentioning
confidence: 99%
“…The PBS method was proposed to detect a significant change in allele or haplotype frequency along the lineage of one population after it diverged from other populations. Many previous studies demonstrated its efficiency in detecting candidate selection signatures in a target population over short divergence times [ 47 49 ]. We finally identified 53,672 candidate selection windows specific to Beijing Black pig and discovered that DNAJC6 and RUFY4 are related to meat quality traits.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the elite yield trials evaluation experiment of four groups of wheat breeding lines including this population in 2019, 78 606 markers were strictly filtered, resulting in 16 072 GBS markers showing the effect of high coverage on trait predictability for subsequent trials [ 70 ]. The high-quality SNPs obtained from 230 garlic germplasms screened by GBS technology were sequenced to infer population structure, and four main groups were found in garlic germplasm [ 71 ]. GBS analysis of 190 young pepper leaves produced only 4083 effective SNPs, which elucidated the origin of Spanish regional varieties and the path of pepper evolution [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only SNPs with MAF ≥ 0.01 [ 70 72 ] and missing rate ≤ 0.1 in a population were used for GWAS. Efficient Mixed-Model Association eXpedited program (EMMAx) was used for GWAS analysis [ 73 ].…”
Section: Methodsmentioning
confidence: 99%